2014
DOI: 10.1371/journal.pone.0111071
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Municipality-Level Mean Income on Access to Aortic Valve Surgery: A Cross-Sectional Observational Study under Japan's Universal Health-Care Coverage

Abstract: BackgroundUniversal health-care coverage has attracted the interest of policy makers as a way of achieving health equity. However, previous reports have shown that despite universal coverage, socioeconomic disparity persists in access to high-tech invasive care, such as cardiac treatment. In this study, we aimed to investigate the association between socioeconomic status and care of aortic stenosis in the context of Japan's health-care system, which is mainly publicly funded.MethodsWe chose aortic stenosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Our study finds that a higher mortality following AVR is related to a lower level of education, primarily within the first year after the procedure. In line with our results, other studies have found minor social disparities in mortality after AVR [2,37,38,47]; however, other studies have found no differences in mortality [33,34]. Common for all the studies are the lack of individual-level information on SES.…”
Section: Socioeconomic Differences In Treatment and Mortalitysupporting
confidence: 87%
See 2 more Smart Citations
“…Our study finds that a higher mortality following AVR is related to a lower level of education, primarily within the first year after the procedure. In line with our results, other studies have found minor social disparities in mortality after AVR [2,37,38,47]; however, other studies have found no differences in mortality [33,34]. Common for all the studies are the lack of individual-level information on SES.…”
Section: Socioeconomic Differences In Treatment and Mortalitysupporting
confidence: 87%
“…There were no differences in comorbidity level for those receiving TAVR versus those treated conservatively. However, in Japan, a country with universal health care coverage, there was no area-based social disparity in the treatment rate of aortic stenosis [33].…”
Section: Socioeconomic Differences In Treatment and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…In most countries, equal access to medical services is a major policy concern for achieving health equity 1 , 2) . However, access to healthcare services is affected by coverage 3) and other factors including socioeconomic circumstances 1 , 4) , care-seeking behaviors 5) , and the behavior of healthcare providers 6) .…”
Section: Introductionmentioning
confidence: 99%
“…In most countries, equal access to medical services is a major policy concern for achieving health equity 1,2) . However, access to healthcare services is affected by coverage 3) and other factors including socioeconomic circumstances 1,4) , care-seeking behaviors 5) , and the behavior of healthcare providers 6) . There is abundant evidence that age, sex 7) , income 8,9) , cohabitation status 10) , ethnicity 11) ,and employment status 12) may affect accessibility of health care.…”
Section: Introductionmentioning
confidence: 99%